Using Sensors with the Internet of Thing for Earthquake Detection System : A Systematic Literature Review - Putri, Shinta Maharani; Asrizal, Asrizal; Amir, Harman; Mairizwan, Mairizwan; Fitri, Mutiara Nurul (Journal of Experimental and Applied Physics, 2024)
Every human being needs safety in their lives from all disasters. However, earthquakes are the most impactful geological natural phenomena that can threaten human safety. One solution is to utilize an earthquake detection system to anticipate such disasters by utilizing sensor technology and the Internet of Thing (IoT). The purpose of this research is to evaluate the effectiveness of various earthquake detection technologies, including vibration sensors such as SW-420, MAG3110, DHT11, ADXL335 Accelerometer, HC-SRO4, and 801S vibration sensor, as well as IoT integration in early warning systems. The method used is Systematic Literature Review (SLR) with PRISMA design, including the steps of identification, screening, eligibility, and analysis of articles taken from the Google Scholar database for publications in 2018-2024. The results showed that the application of technologies such as Fuzzy Logic and vibration sensors, as well as IoT integration, significantly improved the effectiveness of earthquake detection and warning.